2018
DOI: 10.1016/j.jsams.2017.05.018
|View full text |Cite
|
Sign up to set email alerts
|

Profiling of translational and rotational head accelerations in youth BMX with and without neck brace

Abstract: 1Objectives 2 To investigate the influence of BMX helmets and neck braces on translational and 3 rotational accelerations in youth riders. 4 Design 5Mixed model, repeated measure and correlation. 6 Methods 7Twenty three competitive youth BMX riders classified by age group (6-9 yrs, 10-13 yrs 8 and 14-18 yrs) completed 6 laps of an indoor BMX track at race pace, 3 laps without a 9 neck brace (NB) and 3 without brace (WB). A triaxial accelerometer with gyroscope was 10 placed behind the right ear to determine th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
1
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 13 publications
(2 reference statements)
0
12
1
1
Order By: Relevance
“…However, as with BMX, mean peak translational loads were greater than those reported for contact sports 10,11,18,[26][27][28] . Though maximum peak translational loads were not reported for BMX 9 , the present study found these to average ~80 g over the two course, with individual values being recorded up to the 160 g cut off. Whilst the majority of translational accelerations were sub-concussive (10-20 g), 2.3 % of all accelerations recorded were above the reversible threshold for brain injuries 16 .…”
Section: Accepted Manuscriptcontrasting
confidence: 64%
See 3 more Smart Citations
“…However, as with BMX, mean peak translational loads were greater than those reported for contact sports 10,11,18,[26][27][28] . Though maximum peak translational loads were not reported for BMX 9 , the present study found these to average ~80 g over the two course, with individual values being recorded up to the 160 g cut off. Whilst the majority of translational accelerations were sub-concussive (10-20 g), 2.3 % of all accelerations recorded were above the reversible threshold for brain injuries 16 .…”
Section: Accepted Manuscriptcontrasting
confidence: 64%
“…displacements of the head following impulsive neck loads 29 . This is further supported by data from youth BMX riders, which found that those in the eldest of the youth groups were generally had greater neck musculature, resulting in reduced neck loads 30 . This might be the case for Senior and Masters rider, who potentially spend less time on muscular conditioning.…”
Section: Accepted Manuscriptmentioning
confidence: 56%
See 2 more Smart Citations
“…La salud es un tema controversial que interesa a distintas áreas del conocimiento, por lo que este estudio quiso conocer estados del ánimo de sujetos que se enfrentan a potenciales presiones deportivas y que por ende pueden ser vulnerables a desarrollar algún tipo de trastorno, razón por la cual es fundamental conocer el riesgo al que se enfrentan los jóvenes en cuanto a la presencia de la depresión como un trastorno que afecta significativamente la vida del sujeto(Bohórquez, Delgado, & Fernández, 2017).Investigaciones como las de Stucchi(2017), logran demostrar al igual que este estudio que la depresión ha aumentado los últimos años convirtiéndose en una patología juzgada como normal, algunos criterios puestos en evidencia en los corredores del BMX pueden ser alerta para prevenir un suicidio, por ejemplo. Sin embargo, se han venido ignorando a favor de un incremento de tendencia actual(Hurst, et al, 2018).En cuanto a las limitaciones del estudio, se encontró que el número de personas que pertenecen al grupo de corredores de la liga de Tunja de BMX es muy baja, por lo tanto, la muestra es un poco escasa. Sin embargo, se considera la totalidad para la región en cuanto a la práctica oficial del deporte en cuestión.…”
unclassified